(3QSGdI aj CMcGe GdeZUhH dhGQK ZGUHgs - (3GHf MeRI, eMeO Hf MeRI, cGf MjG (B1113 (3g`s ((3eMeO Hf GdMGL Ydj CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai CYde Cf eG TGY Yf HYV GdYhGe GdLGgdjf HLdjGJ GdCMcGe Cfg jMd GdeZUhH dhGQK ZGUHg eY HbGA Yjfg heYQaI UGMHgs
(3BNQgG (B:s
(3jJUOb dbWI GdPej HYO eG eVi eOI GdJYQja Hd jhVY aj HjJ GdeGd dfhGFH GdeSdejfs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B1109 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 268s
(3agQS GdNOjhjI (B7 / 1 402s
(3agQS eNWhWGJ GdXGgQjIs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs